Quy trình dạy học chủ đề “Ứng dụng hình học của tích phân tính diện tích hình phẳng” (Toán 12) với sự hỗ trợ của Manim và Brisk Teaching - Phạm Sỹ Nam, Phạm Sỹ Nam; Ung Nguyễn Thanh Nguyên, Ung Nguyễn Thanh Nguyên (Tạp chí Giáo dục, 2026)
In the context of current educational reforms in secondary schools, visualization tools and AI-generated platforms open up opportunities to enhance teaching effectiveness through vivid, interactive, and personalized learning experiences. This study proposes a teaching process for the topic “Applications of integral geometry to calculate the area of a plane figure" (Mathematics 12) with the support of Manim and the Brisk Teaching AIgenerated platform, and illustrates this process through teaching the content “Calculating the area of a plane figure bounded by the graph of the function y = f(x), the x-axis, and two lines x = a, x = b”. The process describes in detail the Manim scenario to support students in sequentially constructing knowledge; it also presents the design of interactive activities on Brisk Teaching (including: prediction questions, multiple-choice tests, short essays, practice exercises) along with an accompanying automatic assessment mechanism. The proposed teaching process is expected to improve students' conceptual visualization abilities and learning engagement. It can also be replicated and applied to other abstract topics in mathematics.